Mapping of Morphine-Induced OPRM1 Gene Expression Pattern in the Adult Zebrafish Brain - Sivalingam, Mageswary; Ogawa, Satoshi; Parhar, Ishwar S. (Frontiers in Neuroanatomy, 2020)
Morphine is a potent analgesic opiate commonly used in treating acute and chronic pain; however, it has one of the highest addiction and abuse rates. Hence, it is vital to discover its action sites and circuits in the brain to increase the efficacy of morphine treatment. In the present study, we aimed at identifying comprehensive neuroanatomical locations that are sensitive to morphine in the adult zebrafish (Danio rerio). In situ hybridization showed widespread expression of mu opioid receptor (oprm1) gene throughout the brain, including the telencephalon, preoptic area, midbrain, and the hindbrain. Acute morphine exposure induced expression of oprm1 and a neural activity marker gene, npas4a in several brain regions including the telencephalon, preoptic area, and in the hypothalamus. However, morphine exposure reduced npas4a expression in the habenula. These results show that multiple brain regions are sensitive to morphine, which implies functions of morphine beyond the control of pain.